About The Concept Of Competence - Oripova Nodima Halilovna; Bekmanova Mohinur Nurbek qizi (Euro Asian Journal Publishing, 2025)
In today's rapidly developing society, the concept of competence holds great significance for the all-round development of individuals and for achieving both professional and social success. The general concept of competence refers not only to having knowledge, skills, and abilities, but also to the capacity to apply them in practice. Originally emerging from the fields of linguistics and psychology, the concept of competence later entered other domains such as pedagogy, management, and vocational education. This article explores the integration of the concept of general competence into science, its theoretical foundations, structural components, its importance in education and professional development, as well as the processes of its formation and methods of development.
Keywords: infancy; psychological development; attachment theory